Interdependence and democratic legitimation - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 1998)
The premise of the Bellagio Project on Democracy has been that, in recent decades, Western democracies have come to suffer a decline of political "trust" or "confidence" in, or popular "satisfaction" with, the "performance" of their representative institutions, and that this decline needs to be taken seriously as a potential threat to the viability of democratic government (Putnam 1998). The terms used also suggest that the project starts from an implicit principal-agent model in which citizens-as-principals have come to be dissatisfied with the performance of their political agents. If we assume that this is empirically true, and that the change does reflect a deterioration of perceived performance, rather than the rising (or increasingly conflicting) expectations of citizen-principals, there still are two fundamentally different working hypotheses from which one might begin the search for an explanation. Growing dissatisfaction could be caused by factors that have reduced the fidelity of agents – i.e., their willingness to act in the interest of their principals. But it also could be caused by factors that have constrained the objective capacity of agents to achieve the outcomes expected by principals. Whereas the project as a whole is exploring the first of these working hypotheses, my own paper will focus on a particular type of capacity constraints: growing international economic interdependence. In doing so, I will not review the empirical evidence regarding changes in the levels of popular satisfaction, except to note the high degree of variance among countries (Newton, 1998; Katzenstein 1998). Instead, I will examine the analytical and normative arguments that could link economic internationalization to citizen satisfaction, and ultimately to the democratic legitimacy of national political systems. I will argue that one should indeed expect such links to exist, but that their effect on legitimacy will be strongly mediated by the characteristics of national political discourses.
Keywords: 300